(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The research paper provides solution of some exact solution to the Einstein field equation for acceleration free imperfect fluid source with shear viscosity under different conditions. Some physical restriction on the solution have been also discussed.